New technologies in medicine - Gruszka, Jakub; Zwierzyńska, Anna; Komar-Gruszka, Karolina; Adamczyk-Gruszka, Olga (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2022)
The development of new technologies gives the opportunity to create innovative methods, the application of which in medicine may turn out to be a breakthrough. These techniques can be used at many levels of the diagnostic and therapeutic process, ranging from interview collecting and ending with home treatment of the patient. Recently, it has become more and more common to use telecommunications tools combining many digital technologies. Telemedicine developed significantly during the COVID-19 pandemic, when the number of contact medical visits was limited due to the epidemiological threat. New technologies, however, are not only digital communication. Artificial intelligence is increasingly used in medicine to facilitate the diagnostic process. The applied algorithms make it possible to detect defects at the stage imperceptible with the use of conventional methods.